Hyperphosphataemia in 2019: have we made progress?. Issue 5 (September 2019) - Hutchison, Alastair J.; Wald, Ron; Hiemstra, Thomas F.
Abstract : Purpose of review: This review describes recent developments in the management of serum phosphate in dialysis patients, with a focus on the development of recent trials which randomize patients to different levels of control. Recent findings: We review the uncertainties around clinical benefits of serum phosphate control and alternative approaches to current management, as well as a multinational attempt to conduct randomized controlled trials in this area. We discuss novel methods of limiting oral phosphate absorption. Summary: Although numerous guidelines and target ranges for serum phosphate management exist, they are largely based on observational data and there is no definitive evidence that good control improves the length or quality of life of dialysis patients. New phosphate binders continue to appear on the market with increasing financial cost but without additional meaningful outcome data. Two recently published trials have demonstrated the feasibility of a large-scale study of differing phosphate levels to test the hypothesis that reduction of serum phosphate is beneficial to dialysis patients. Restriction of oral phosphate intake should not be overlooked.